2018
DOI: 10.1002/ajhb.23115
|View full text |Cite
|
Sign up to set email alerts
|

Circadian cortisol dynamics across reproductive stages and in relation to breastfeeding in the Philippines

Abstract: These findings are consistent with known alterations in hypothalamic-pituitary-adrenal axis function during reproduction, and in particular point to marked and progressive elevation in maternal cortisol during the course of gestation. Cortisol appears to return to nulliparous levels after parturition, with levels suppressed below nulliparous levels during lactation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Estrogen and progesterone drop suddenly after childbirth, but prolactin levels remain high, especially in breastfeeding mothers [ 1 ]. Moreover, breastfeeding further reduces estrogen and cortisol levels [ 15 , 16 ]. Changes in hormone levels lead to a strong immune tolerance during pregnancy, while the immune environment shifts to a proinflammatory state at the end of pregnancy and postpartum.…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen and progesterone drop suddenly after childbirth, but prolactin levels remain high, especially in breastfeeding mothers [ 1 ]. Moreover, breastfeeding further reduces estrogen and cortisol levels [ 15 , 16 ]. Changes in hormone levels lead to a strong immune tolerance during pregnancy, while the immune environment shifts to a proinflammatory state at the end of pregnancy and postpartum.…”
Section: Discussionmentioning
confidence: 99%
“…This difference can be observed in terms of cortisol value and the time course of hormone secretion after stress (Kudielka, Hellhammer, & Wist, ). Thayer, Agustin, and Kuzawa (), found in their study that the cortisol levels among women in the last trimester of pregnancy were significantly higher but these levels in the breastfeeding period were lower than the levels before the pregnancy. The difference in terms of cortisol values in the studies was thought to be caused by the time when the cortisol samples were taken from the study group.…”
Section: Discussionmentioning
confidence: 88%
“…This study demonstrates promising protection from exclusive breastfeeding in a stressful environment. Another study in 741 women found consistently lower cortisol levels at wake and at night in breastfeeding women compared to non-breastfeeding or nulliparous women up to 1 year after delivery [39].…”
Section: Discussionmentioning
confidence: 92%